Comparative Legal Analysis of Hospital-Based and University-Based Specialist Medical Training Models - Prima Maharani Putri; Emirza Nur Wicaksono; Rosiana Nurwa Indah; Vashti Resti Putri Firdaus (Kosmik Hukum, 2026)
This study comparatively examines the hospital-based and university-based models of Specialist Medical Doctor Professional Education (Pendidikan Profesi Dokter Spesialis/PPDS) in Indonesia from the perspective of regulatory frameworks and legal protection. Using normative (doctrinal) legal research, it analyzes the Health Law of 2023, Ministry of Health Regulation No. 13 of 2022, Ministry of Education, Culture, Research, and Technology Regulation No. 53 of 2023, and other relevant legal instruments. The analysis demonstrates that the hospital-based model provides weaker legal protection due to the unclear legal status of PPDS participants, whereas the university-based model offers greater legal certainty by recognizing participants as students, despite remaining ambiguities in the allocation of legal responsibilities between universities and teaching hospitals. The study recommends harmonizing the regulatory framework by explicitly defining the legal status of PPDS participants, clarifying institutional responsibilities, and strengthening legal protection and social security mechanisms. This study contributes to the legal scholarship on medical education by providing the first comparative normative analysis of Indonesia's dual PPDS models and offers a legal framework to support future regulatory reform aimed at enhancing legal certainty, institutional accountability, and the protection of specialist medical trainees.